United Nations efforts to achieve sustainable development - Hana Almabrouk Khalifa Altayari (Journal of Libyan Academy Bani Walid, 2025)
Sustainable development is a matter of great interest to members of the international community, particularly the United Nations and its role in establishing the parameters of the concept of sustainable development. The United Nations is one of the most prominent international organizations responsible for promoting peace and development worldwide. Among its primary objectives is achieving sustainable development. The United Nations has made significant efforts to achieve the 2030 Agenda for Sustainable Development, which includes 17 key goals: eradicating poverty and hunger, protecting the environment, achieving justice and equality, improving the quality of education and health care, and promoting climate action. The United Nations works through its agencies and bodies, such as the United Nations Development Program, the Food and Agriculture Organization, the General Assembly, and the Security Council, as mechanisms aimed at implementing the Sustainable Development Plan. Despite the efforts made by the United Nations, it faces several major challenges, especially in light of global crises. The United Nations continues to push the world towards a more sustainable and just future.